2009
DOI: 10.1021/jp9049582
|View full text |Cite
|
Sign up to set email alerts
|

Continuously Infusing Hyperpolarized 129Xe into Flowing Aqueous Solutions Using Hydrophobic Gas Exchange Membranes

Abstract: Hyperpolarized (HP) 129 Xe yields high signal intensities in magnetic resonance (MR) and, through its large chemical shift range of ∼300 ppm, provides detailed information about the local chemical environment. To exploit these properties in aqueous solutions and living tissues requires the development of methods for efficiently dissolving HP 129 Xe over an extended time period. To this end, we have used commercially available gas exchange modules to continuously infuse concentrated HP 129 Xe into flowing liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 58 publications
0
40
0
Order By: Relevance
“…Hp 129 Xe, with high tissue solubility and 300 ppm chemical shift range (Goodson, 2002), has been explored to study gas exchange in lungs (Ruppert et al ., 2000; Driehuys et al ., 2006; Ruppert et al ., 2007; Driehuys et al ., 2009; Cleveland et al ., 2010). Hp 129 Xe was also explored for molecular imaging using functionalized xenon biosensors (Hilty et al ., 2006; Schroder et al ., 2006) and was infused directly into blood for MR imaging applications (Cleveland et al ., 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Hp 129 Xe, with high tissue solubility and 300 ppm chemical shift range (Goodson, 2002), has been explored to study gas exchange in lungs (Ruppert et al ., 2000; Driehuys et al ., 2006; Ruppert et al ., 2007; Driehuys et al ., 2009; Cleveland et al ., 2010). Hp 129 Xe was also explored for molecular imaging using functionalized xenon biosensors (Hilty et al ., 2006; Schroder et al ., 2006) and was infused directly into blood for MR imaging applications (Cleveland et al ., 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Cryogenic separation complicates the operational procedures for clinical and preclinical hp 129 Xe MRI. For a number of applications a repeat noble gas delivery at high polarization and concentration levels is needed (6,(30)(31)(32)(33)(34)(35). Additionally, a very constant level of spin polarization is required for molecular imaging with hp 129 Xe biosensors using the hyperpolarized xenon chemical exchange saturation transfer (HyperCEST) methodology (17,(36)(37)(38).…”
mentioning
confidence: 99%
“…As only low N 2 pressure was applied, we may assume that the N 2 gas volume that entered the Plexiglas cylinder compressed the collapsing Tedlar bag such that an identical Xe volume flowed from the bag toward the RF coil. This setup achieved a sufficiently constant Xe flow without requiring additional flow restrictors [12]. …”
Section: Methodsmentioning
confidence: 99%
“…Thus, to extend the acquisition times in meaningful ways, the magnetization in the storage reservoir must exhibit a sufficiently long longitudinal relaxation time, T1R. Previous work has demonstrated that sufficient signal continuity may not be achieved due to relaxation during HP gas storage in flexible fluoropolymer bags, which are used extensively in MRI [12]. Moreover, T1R in itself may not stay constant but rather may change while the bag is being deflated [13].…”
Section: Introductionmentioning
confidence: 99%